Aplikatif Interpretasi Tekstual pada Kandungan Hadis - Setiawan, Ahmad Siddiq; Ismail Ahmad, La Ode; Amin, Muhammadiyah; Alwi, Zulfahmi (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2024)
This article discusses the applicative textual interpretation of the content of Hadith. The Hadith of the Prophet Muhammad plays a significant role in Islam as a guiding principle in life and as a source of practice in daily life. Understanding the content of Hadith requires a certain approach to avoid misunderstandings in practicing a Hadith. The abundance of misconceptions in understanding Hadith without proper approach leads to a blame game, resulting in numerous problems and conflicts due to differences in understanding, which breed mutual animosity among individuals. Understanding Hadith while considering various aspects is declining. This research presents applicative textual interpretation through several Hadith to understand the content of Hadith from the aspects of creed, worship, law, exhortation and deterrence, and guidance. This research is a qualitative study through library research, collecting data from primary sources and relevant books. This research is expected to contribute to the discourse and educate the public to understand Hadith carefully to reduce problems caused by misunderstandings in understanding the content of the Prophet's Hadith texts. Additionally, it is hoped to encourage academics to further develop research related to textual interpretation of Hadith content.